Model Aplikasi Stimulasi Deteksi dan lntervensi Dini Tumbuh Kembang Anak Berbasis Web - Buang Budi Wahono (STMIK Banjarbaru, 2022)
The Indonesian Ministry of Health has collaborated with the Indonesian Pediatrician Association (IDAI) since 2007 to develop an instrument for early growth and development stimulation, detection and intervention for children which is described in the Guidelines for the Implementation of Stimulation, Detection and Early Intervention on Child Growth and Development (SDIDTK) at the Primary Health Service Level. The obstacles encountered in implementing SDIDTK include recording and reporting that have not gone well. The SDIDTK for Children's application with several menus has been created as a web application using the PHP language with the Laravel framework. The results of the implementation are in accordance with the design and the program modules are functioning properly. which is designed starting with the design of the display includes use case diagrams, interfaces design, to the coding and testing stages. Tests show this application runs as expected, and there are no logical or calculation errors. Test results show this application is very feasible to use.Keywords: Application Software; Unified Modelling Language; Laravel framework; Blackbox testing AbstrakKementerian Kesehatan Indonesia bekerjasama dengan lkatan Dokter Anak Indonesia (IDAI) sejak tahun 2007 menyusun instrumen stimulasi, deteksi dan intervensi dini tumbuh kembang untuk anak yang dijabarkan dalam Pedoman Pelaksanaan Stimulasi, Deteksi dan lntervensi Dini Tumbuh Kembang (SDIDTK) Anak pada Tingkat Pelayanan Kesehatan Dasar. Kendala pelaksanaan SDIDTK yang ditemui diantaranya pencatatan dan pelaporan yang belum berjalan dengan baik. Aplikasi SDIDTK Anak dengan beberapa menu telah dibuat sebagai aplikasi berbasis Web menggunakan bahasa pemrograman PHP dengan framework Laravel. Hasil dari implementasi sesuai dengan perancangan dan modul-modul program berfungsi dengan baik, yaitu dirancang dimulai dengan perancangan tampilan meliputi use case diagram, desain interfaces, sampai tahap pengkodean dan pengujian. Pengujian menunjukkan aplikasi ini berjalan sesuai dengan yang diharapkan, dan tidak ada kesalahan logika maupun perhitungan. Hasil pengujian menunjukkan aplikasi ini sangat layak untuk digunakan.